Efforts to Improve Indonesian Learning Achievement in Reading Materials Using the Role-Playing Method in Class XI of the Special State School of Trustees in the Province of East Kalimantan - Widayati, Harni (Educationist: Journal of Educational and Cultural Studies, 2022)
Child with Intellectual Disability (ID) is a child below average intelligence, experiences behavioural obstacles, adjustments and occurs during his development. Children’s with Intellectual Disability are often equated with mentally retardation terms (Feeble Minded). Reading using the role-playing method is one of the main lessons that teachers give to children at school. The lesson, which is a part of Bahasa course, is given early as a basis for further learning. Children who cannot read yet have difficulty following other lessons. The purpose of this classroom action research is entitled " Efforts to Improve Achievement of Learning Indonesian in Reading Material by Applying the Role-Playing Method in Class XI SLB Negeri Pembina, east Kalimantan Province " is to get an overview of the implementation of learning Indonesian in reading in children at SMPLB SLB N Pembina, east Kalimantan Province and the difficulties faced by the teacher. in improving the implementation of learning to read in mentally retarded children. In this classroom action research, the subjects of this study were five students with in class XI and the data collection techniques used were observation and test. Furthermore, the research results were analysed using quantitative and qualitative analysis techniques.